New directions in educational ethnography - Hopson, Rodney K.; Kaul, Akashi; Rodick, William (Studies in educational ethnography ;, 2016)
Volume 13 relaunches the book series after a 9-year hiatus and addresses new directions in the field of educational ethnography. The authors in the book share methodological similarities, but their applications, contexts, treatments, and contributions to the field as evidenced here are unique and vary considerably. The diversity of views and perspectives of ethnographic theory and method in educational settings are on full display, from the street to urban and suburban classrooms and to college settings, where gender, race, class, and power dynamics impact learners, teachers, parents, and communities. Taken together, the chapters reinvigorate and redirect a new set of possibilities and opportunities in ethnographic research, while highlighting shifts, problems and new directions for the field.